Digitalization of prevention and treatment and the combination of western and Chinese medicine in management of acute heart failure - Wang, Yingxin; Cui, Herong; Li, Liwen; Cao, Yajing; Qu, Hanyun; Ailina, Halisi; Dou, Zhili; Tang, Chuwei; Qin, Wanli; Wang, Chenlu; Yang, Xue; Feng, Shixing; et al. (Frontiers in Cardiovascular Medicine, 2023)
Digitalization has emerged as a new trend in healthcare, with great potential and creating many unique opportunities, as well as many challenges. Cardiovascular disease is one of the major causes of disease-related morbidity and mortality worldwide, and the threat to life posed by acute heart failure is evident. In addition to traditional collegiate therapies, this article reviews the current status and subdisciplinary impact of digital healthcare at the level of combined Chinese and Western medical therapies. It also further discusses the prospects for the development of this approach, with the objective of developing an active role for digitalization in the combination of Western and Chinese medicine for the management of acute heart failure in order to support maintenance of cardiovascular health in the population.